Volume 4: Computational Fluid Dynamics, Neutronics Methods and Coupled Codes; Student Paper Competition 2006
DOI: 10.1115/icone14-89237
|View full text |Cite
|
Sign up to set email alerts
|

Pressure Drop Correlations of Single-Phase and Two-Phase Flow in Rolling Tubes

Abstract: A series of experimental studies of frictional pressure drop for single phase and two-phase bubble flow in smooth rolling tubes were carried out. The tube inside diameters were 15mm, 25mm and 34.5mm respectively, the rolling angles of tubes could be set as 10° and 20°, and the rolling periods could be set as 5s, 10s and 15s. Combining with the analysis of single-phase water motion, it was found that the traditional correlations for calculating single-phase frictional coefficient were not suitable for the rolli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Studies of Cao et al [4] and Xing et al [10] indicated that rolling motion affected fluctuation of resistance characteristics for two following reasons. On the one hand, the spatial position of rod bundle varies periodically, giving rise to the periodical variations of lateral and axial component of gravity.…”
Section: Effect Of Rolling Parametersmentioning
confidence: 98%
See 1 more Smart Citation
“…Studies of Cao et al [4] and Xing et al [10] indicated that rolling motion affected fluctuation of resistance characteristics for two following reasons. On the one hand, the spatial position of rod bundle varies periodically, giving rise to the periodical variations of lateral and axial component of gravity.…”
Section: Effect Of Rolling Parametersmentioning
confidence: 98%
“…By reviewing some open literatures on thermo-hydraulic characteristics of ship nuclear reactors under ocean conditions, Ma et al [3] pointed out that the rolling motion was the most typical movement among ocean conditions and its effect on fluid flow was most complex. Cao et al [4] investigated the transient frictional resistance of single-and two-phase flow in rolling circular tubes, and indicated that the conventional correlations provided poor predictions of the transient frictional resistance. Combining transient single-phase frictional coefficient correlation with homogeneous flow model, they proposed correlation for calculating two-phase frictional pressure drop of bubbly flow under rolling condition.…”
Section: Introductionmentioning
confidence: 99%
“…Their results indicate that the rolling motion may affect the thermal hydraulic behaviors of nuclear reactor system, and the present empirical correlations could not capture the flow and heat transfer characteristics under rolling motion condition. Cao et al (2006) and Zhang et al (2009) experimentally studied the influences of rolling parameters, flow rates and tube sizes on single-phase flow resistance in forced circulation. They believe that the flow rate of forced circulation is nearly invariable even under rolling condition.…”
Section: Introductionmentioning
confidence: 99%
“…During rolling process of a marine reactor, an inertial force is imposed on the primary coolant, therefore, a number of previous investigations concerning single-phase flow behaviors under rolling condition have been performed (see e.g. Cao et al, [2] ; Gao et al, [3] ; Murata et al, [4] ; Tan et al, [5] ; Xing et al, [6] ; Yan et al, [7,8] ; Zhang et al, [9] ). The effect of rolling amplitude, rolling period, and flow rate as well as tube size on single-phase flow resistance was studied experimentally and theoretically, indicating that the effect of rolling motion on single-phase flow resistance and heat transfer shouldn't be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Cao et al [2] , Luan et al [11] , Wang et al [12] and Zhang et al [13] studied the two-phase flow pattern and frictional resistance in pipes under rolling condition experimentally. Their results showed that the rolling period, rolling amplitude and channel size affect the transitions between flow patterns, especially from the bubble to slug flow and churn to annular flow.…”
Section: Introductionmentioning
confidence: 99%